Zapisz Wyrażenia w jak najprostszej postaci.

a) 9(x-6) +4(x + 13)
b) 2x (x +4 ) + 6x (x+11 )

2 2
c) 3 (x + 2x - 1 ) + 5x (2x - 6x - 3 )

2 2
d) 4x ( x+6 ) - 12x (x + 9x -1 )

2 2
e) 7x (8x - 1 ) - 7x (8x + 1 )

2
f) -2x ( - 1x + 1 ) - 1x (8x -4 )
8 12 4

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-29T17:41:37+01:00
A) 9(x-6) +4(x + 13)
= 9x - 54 + 4x + 52
= 13x - 2

b) 2x (x +4 ) + 6x (x+11 )
= 2x kwadrat + 8x + 6x kwadrat + 66x
= 8x kwadrat + 74x

c) 3 (x + 2x - 1 ) + 5x (2x - 6x - 3)
= 3x + 6x - 3 + 10x kwadrat - 30x kwadrat - 15x
= - 6x - 20x kwadrat -3

d) 4x ( x+6 ) - 12x (x + 9x -1 )
= 4x kwadrat + 24x - 12x kwadrat - 108x kwadrat + 12x
= - 116x kwadrat + 36x

e) 7x (8x - 1 ) - 7x (8x + 1 )
= 56x kwadrat -7x -56x kwadrat - 7x
= -14x

f) -2x ( - 1x + 1 ) - 1x (8x -4 )
= 2x kwadrat - 2x - 8x kwadrat + 4x
= - 6x kwadrat + 2x
2010-01-29T17:48:17+01:00
A) 9(x-6) +4(x + 13)=9x-54+4x+52=13x-2
b) 2x (x +4 ) + 6x (x+11 )=2x kwadrat+8x+6x kwadrat+66x=
8x kwadrat +74x
c) 3 (x + 2x - 1 ) + 5x (2x - 6x - 3 )=
=3x+6x-3+10x kwadrat-30x kwadrat-15x=-6x-20x kwadrat-3
d) 4x ( x+6 ) - 12x (x + 9x -1 )=
=4xkwadrat+24x - 12x kwadrat + 108x -12x =
=-8xkwadrat+120x
e) 7x (8x - 1 ) - 7x (8x + 1 )=
=56x kwadrat-7x-56x kwadrat-7x= -14x
f) -2x ( - 1x + 1 ) - 1x (8x -4 )=
=2x kwadrat-2x-8x kwadrat+4x=
=-6x kwadrtat+2x